Covid-19 dan Gerakan Sosial Perempuan - Ujang Wardi; Elfia Elfia (Indonesian Center for Religion and Society Studies (InTReSt), 2021)
This study explains how social movements are initiated by women's groups. The movement carried out penetrates various spaces in the social environment and even traditional institutions as groups that have authority. Through a descriptive approach and in-depth interview techniques, this study answers questions about how women's groups carry out social movements by constructing the issue of the non-transparent distribution of Covid-19 aid. Thus, the mobilizing structure, which is carried out systematically, attracts traditional institutions (ninik mamak) in the vortex of conflict. This study found that the sources of issues from social movements carried out by women's groups were (a) information from the deputy governor regarding the distribution of Covid-19 aid, (b) nepotism and collusion from the nagari government. Two framing issues (framing) are then packaged through social media to attract the power to carry out mass actions (demonstrations). This study concludes that the demonstration of women giving birth is a new policy related to the distribution of Covid-19 by the government.